A preliminary study of donax arundastrum Extracts on haematological parameters - Abdullah, Mardiaty Iryani (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
This study was conducted with the objective of determining the effect of Donax arundastrum extracts (Bemban) on haematological parameters. The plant was obtained from swampy and lowland areas in Tumpat, Kelantan. Information regarding the plant was obtained from the inhabitants of the village nearby the collection sites. Subsequently the plant was extracted using water and ethanol based extraction techniques. Rhizome part of the plant was used for this preparation. Small pieces of rhizome was dried in hot air oven and ground into powdered form. The extraction of powdered material was performed with organic and non-organic solvents. The organic solvent used was absolute ethanol and distilled water as non-organic or aqueous solution. The procedure involved the use of Soxhlet apparatus for water based extraction and immersing the sample with absolute ethanol. In obtaining the powder extracts, the techniques employed include filtration, saturation and freeze-drying. Water and ethanol extract of Donax arundastrum rhizome at the concentration of 0.05 mg/ml was then tested on fresh blood. Calculation of dosage was done based on the amount of powdered extract, volume of solvent and blood volume to be tested. The study was conducted on 5 fresh blood samples obtained from healthy volunteer donors. The blood samples were tested after adding the extract at 0 minute, 30 minutes, 60 minutes, 90 minutes and 120 minutes intervals. Haematology analyzer was used to analyze the haematological parameters. Analysis of haematological parameter was done based on the changes occurred following treatment with the extract at the different time intervals.